A cold sprayed copper tungsten graphene coating, method of making and use thereof
Patent Information
- Application Number
- CN202410358524.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-27
AI Technical Summary
[0004]针对现有技术的缺陷,本申请的目的在于提供一种超低摩擦系数、磨损率与超高抗铝黏附能力的冷喷涂铜钨石墨烯涂层、其制备方法和在电磁发射轨道中的应用,用于解决电磁发射轨道铜合金材料存在COF较高、耐磨性能较低、铝黏附现象严重、寿命短的问题
[0019]本申请提供了一种超低摩擦系数、磨损率与超高抗铝黏附能力的冷喷涂铜钨石墨烯涂层的制备方法,以CuCrZr合金粉末、W粉和石墨烯纳米片的混合粉末作为原料,通过高压冷喷涂在基底上喷涂制备得到。实验证明,这三种粉末的结合能够综合W颗粒高强度、硬度和石墨烯良好自润滑能力的优点,使复合涂层的COF能够降低至0.16,磨损率相对于基底降低一个数量级以上。高压冷喷涂不仅能够减少颗粒结合不良好引起的孔洞等缺陷,还能够提高成形件的致密度和涂层质量,减少后续零件处理工序,解决铜基导轨耐磨性差、铝黏附现象严重的问题。
Smart Images

Figure CN118256905B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of copper-based track wear-resistant coatings for electromagnetic launch equipment, and more specifically, relates to a cold-sprayed copper-tungsten graphene coating, its preparation method and application. Background Technology
[0002] As one of the most important components of electromagnetic launch equipment, the performance and lifespan of the launch track determine the overall performance and service life of the electromagnetic launch system. Currently, the most commonly used material for electromagnetic launch tracks is a CuCrZr high-conductivity copper alloy with a COF of approximately 0.6 and a wear rate of around 10%. -4 mm 3 The electromagnetic rail is on the order of N·m and will exhibit severe aluminum adhesion. Due to the harsh service environment of high current, instantaneous high temperature, strong magnetic field and large lateral force during launch, it is prone to damage in the form of wear, planing, ablation and adhesion, and even severe aluminum adhesion.
[0003] With the development of electromagnetic launch power supply technology, electromagnetic launch rails need to be more lubricated, more wear-resistant, more stable, and have a longer lifespan. This places higher demands on electromagnetic launch copper rails. However, the copper alloy materials currently widely used in the manufacture of electromagnetic launch rails have disadvantages such as high COF, low wear resistance, severe aluminum adhesion, and short lifespan. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the purpose of this application is to provide a cold-sprayed copper-tungsten graphene coating with ultra-low friction coefficient, wear rate and ultra-high anti-aluminum adhesion capability, its preparation method and its application in electromagnetic launch orbits, in order to solve the problems of high COF, low wear resistance, severe aluminum adhesion and short life of copper alloy materials in electromagnetic launch orbits.
[0005] To achieve the above objectives, this application provides a method for preparing a cold-sprayed copper-tungsten graphene coating, which uses a mixture of CuCrZr alloy powder, W powder and graphene nanosheets as raw materials and is prepared by high-pressure cold spraying onto a substrate.
[0006] Preferably, the CuCrZr alloy powder in the mixed powder has a particle size of 10–100 μm, and the W powder has a particle size of less than or equal to 8 μm; the graphene nanosheets have a specific surface area of 200–400 m². 2 / g.
[0007] Preferably, the mass ratio of CuCrZr alloy powder, W powder and graphene nanosheets in the mixed powder is (160-200):(100-140):(0.5-2).
[0008] Preferably, the mixed powder of CuCrZr alloy powder, W powder, and graphene nanosheets is obtained according to the following method:
[0009] A portion of CuCrZr alloy powder and graphene nanosheets are first ball-milled and mixed to obtain graphene-copper alloy composite powder. Then, the prepared graphene-copper alloy composite powder is mixed with W powder and the remaining CuCrZr alloy powder to obtain the mixed powder.
[0010] More preferably, the portion of CuCrZr alloy powder accounts for 40-80 wt% of the total CuCrZr alloy powder.
[0011] Preferably, the CuCrZr alloy powder contains 0.1-0.8% Cr by mass, 0.05-0.25% Zr by mass, and the balance is Cu.
[0012] Preferably, the high-pressure cold spraying uses high-purity nitrogen or high-purity argon as the spraying gas.
[0013] The pressure inside the spraying chamber is 4.5–4.8 MPa, the chamber temperature is 750–800℃, the spraying distance is 28–32 mm, and the gun speed is 275–325 mm / s.
[0014] According to another aspect of the present invention, a cold-sprayed copper-tungsten graphene coating prepared by the preparation method described above is provided.
[0015] According to another aspect of the invention, an electromagnetic launch track is provided, the surface of which is provided with the aforementioned cold-sprayed copper-tungsten graphene coating.
[0016] Preferably, the thickness of the cold-sprayed copper-tungsten graphene coating is 500–1000 μm.
[0017] Preferably, the substrate is a dispersion-strengthened copper alloy or beryllium copper.
[0018] In summary, compared with the prior art, the technical solutions conceived in this application have the following main technical advantages:
[0019] This application provides a method for preparing a cold-sprayed copper-tungsten graphene coating with ultra-low friction coefficient, wear rate, and ultra-high anti-aluminum adhesion capability. The method uses a mixed powder of CuCrZr alloy powder, W powder, and graphene nanosheets as raw materials, and prepares the coating by high-pressure cold spraying onto a substrate. Experiments show that the combination of these three powders integrates the advantages of high strength and hardness of W particles and the good self-lubricating ability of graphene, reducing the COF of the composite coating to 0.16 and lowering the wear rate by more than an order of magnitude relative to the substrate. High-pressure cold spraying not only reduces defects such as voids caused by poor particle bonding but also improves the density and coating quality of the formed parts, reduces subsequent part processing steps, and solves the problems of poor wear resistance and severe aluminum adhesion in copper-based guide rails. Attached Figure Description
[0020] Figure 1 This is a SEM image of the mixed powder Cu40W-GNPs powder in Example 1 of the present invention.
[0021] Figure 2 The images show the XRD phase diagrams of Cu40W powder and coating in Example 1 of this invention and Cu40W-GNPs powder and coating in Comparative Example 1.
[0022] Figure 3 The image shows the Raman diagram of the graphene nanosheets and Cu40W-GNPs coating in Example 1 of this invention.
[0023] Figure 4 The images show the friction and wear curves of samples ODS Cu, Cu40W, and Cu40W-GNPs from Example 1 and Comparative Example 1 of this invention.
[0024] Figure 5 The wear rate diagrams are for samples ODS Cu, Cu40W, and Cu40W-GNPs in Example 1 and Comparative Example 1 of this invention.
[0025] Figure 6 This is a graph showing the aluminum adhesion ratio of samples ODS Cu, Cu40W, and Cu40W-GNPs in Example 1 and Comparative Example 1 of the present invention.
[0026] Figure 7 The image shows the SEM image of the composite powder prepared in Comparative Example 2. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0028] The present invention provides a method for preparing a cold-sprayed copper-tungsten-graphene coating, which uses a mixture of CuCrZr alloy powder, W powder and graphene nanosheets as raw materials, and prepares the copper-tungsten-graphene composite coating by high-pressure cold spraying on a substrate.
[0029] In some embodiments, the CuCrZr alloy powder in the mixed powder has a particle size of 10–100 μm, more preferably 12–80 μm; the W powder has a particle size of less than or equal to 8 μm, exhibiting a normal distribution, more preferably less than or equal to 5 μm; and the graphene nanosheets have a specific surface area of 200–400 m². 2 / g, preferably 275-330m 2 / g.
[0030] In some embodiments, the CuCrZr alloy powder contains 0.1–0.8% Cr by mass, 0.05–0.25% Zr by mass, and the balance is Cu. The CuCrZr alloy powder can be purchased commercially or obtained through methods such as gas atomization powdering or electrolytic powdering. Due to limitations in the alloy copper powder preparation process, the content of each element in the obtained CuCrZr alloy powder (or alloy copper powder) is within a certain range.
[0031] The mixed powder of CuCrZr alloy powder, W powder and graphene nanosheets in this application is obtained by the following method: a portion of CuCrZr alloy powder and graphene nanosheets are first ball-milled and mixed to obtain graphene copper alloy composite powder, and then the obtained graphene copper alloy composite powder is mixed with W powder and the remaining CuCrZr alloy powder to obtain the mixed powder.
[0032] Considering the high hardness of W powder, in a preferred embodiment, a portion of CuCrZr alloy powder (40-80 wt% of all CuCrZr alloy powder) and graphene nanosheets are first ball-milled and mixed for 3-6 hours to obtain graphene-copper alloy composite powder. Then, the prepared graphene-copper alloy composite powder is mixed with W powder and the remaining CuCrZr alloy powder to obtain a mixed powder. In a preferred embodiment, the planetary ball mill mixing is carried out under an argon protective atmosphere. When mixing the prepared graphene-copper alloy composite powder with W powder and the remaining CuCrZr alloy powder, ball milling or ordinary mechanical mixing methods, such as vibration or mechanical stirring, can be used. For example, vibration mixing can be used at a speed of 100-200 rpm for 10-30 minutes.
[0033] In some embodiments, the mass ratio of CuCrZr alloy powder, W powder and graphene nanosheets in the mixed powder is (160-200):(100-140):(0.5-2), more preferably (170-190):(110-130):(0.8-1.2).
[0034] In some embodiments, the high-pressure cold spraying uses high-purity nitrogen or high-purity argon as the spraying gas (i.e., the spraying acceleration gas); the pressure inside the spraying chamber is 4.5–4.8 MPa, the chamber temperature is 750–800°C, the spraying distance (the distance between the spray gun nozzle and the substrate surface) is 28–32 mm, and the gun travel speed is 275–325 mm / s.
[0035] When performing high-pressure cold spraying in this application, the spraying gas can be nitrogen or argon; any gas that can accelerate the powder can be used. The above process parameters, combined with the spraying distance, achieve high coating density and eliminate defects. The cold spraying process can also be adjusted according to the composition of the protective material.
[0036] The cold-sprayed copper-tungsten graphene coating prepared by this invention can be used on the surface of electromagnetic launch tracks. In application, this coating is directly sprayed onto the electromagnetic launch track, resulting in an electromagnetic launch track with ultra-low friction coefficient, wear rate, and ultra-high resistance to aluminum adhesion. The electromagnetic launch track can be made of various feasible materials, such as copper alloys with good conductivity and high strength, including but not limited to dispersion-strengthened copper alloys such as ODS alumina copper (ODS Cu alloy) and beryllium copper. The ODS Cu alloy matrix includes, but is not limited to, grades C15715, C15720, C15725, and C15760, corresponding to different aluminum and alumina contents.
[0037] In some embodiments, when the above-mentioned mixed powder of the present invention is applied to the surface of a high-conductivity copper alloy track substrate by high-pressure cold spraying, an electromagnetic launch track coated with a coating is obtained. In some embodiments, the thickness of the cold-sprayed copper-tungsten graphene coating is 500-1000 μm.
[0038] In some practical engineering applications, a method and product for cold-spraying copper-tungsten graphene coatings with ultra-low friction coefficient, wear rate, and ultra-high resistance to aluminum adhesion may include the following specific steps:
[0039] (1) Two alloy systems, CuCrZr alloy powder and W powder, were prepared using a high-pressure argon atomization powder preparation device. First, a 900-mesh stainless steel sieve was used to remove larger particles from the CuCrZr powder, followed by a 270-mesh steel sieve to remove smaller particles, resulting in spherical CuCrZr powder with a particle size between 15-53 μm and good flowability, thus obtaining initial powder with good sphericity and flowability. For W powder, a 2500-mesh steel sieve was used to remove larger particles, resulting in non-spherical tungsten powder with a particle size of approximately 5 μm. Graphene nanosheets were purchased from TOKYO CHEMICAL INDUSTRY CO., LTD. The flowability was determined by the rolling speed of the composite powder in the container.
[0040] (2) Under a protective atmosphere, the CuCrZr powder and graphene nanosheets were mixed using a QM-3SP2 planetary ball mill at a low energy level. The planetary ball mill was stopped after a set time, and then restarted after a set time, repeating this process until 5 hours of mixing were achieved. Immediately afterwards, the graphene copper alloy composite powder, the remaining CuCrZr alloy powder, and W powder were mixed using a simple shaking method until 15 minutes were achieved.
[0041] (3) After loading the powder into the high-pressure cold spray powder feeder, first adjust the main air flow control valve on the control panel to the maximum, then adjust the pressure reducer on the main air control pipe to make the main air pressure output 4MPa, then adjust the pressure reducer on the powder feeding gas control pipe to make the powder feeding gas pressure about 0.5MPa higher than the main air pressure, and then start spraying.
[0042] (4) The composite powder was prepared using a high-pressure cold spraying device with high-purity N2 as the spraying gas. The chamber pressure was 4.5–4.8 MPa, the chamber temperature was 750–800 °C, the spraying distance was 28–32 mm, and the gun speed was 275–325 mm / s. The optimal process for cold spraying the composite coating was determined based on the density of the manufactured sample.
[0043] This invention uses a mixed powder of CuCrZr alloy powder, tungsten powder, and graphene nanosheets as raw materials, and prepares a composite coating using a high-pressure cold spraying method. Through room temperature tribological tests and three-dimensional white light interferometry, SEM observation, and statistical analysis of the aluminum adhesion area on the wear track surface, it was found that the composite coating has a relatively low and relatively stable COF (0.16) and a relative COF (ODS Cu) of 24.8 × 10⁻⁶. -5 mm 3 / N·m) reduces the wear rate by more than an order of magnitude (1.9×10 -5 mm 3With its superior anti-aluminum adhesion capability (N·m) and a 40-fold reduction in aluminum adhesion area relative to the substrate (ODS Cu), it solves the problem of limited tribological performance of copper-tungsten coatings.
[0044] To illustrate the method of the present invention in more detail, the following detailed description is provided in conjunction with specific embodiments.
[0045] Example 1
[0046] Two alloy systems, CuCrZr alloy powder and W powder, were prepared using a high-pressure argon atomization powder preparation device. In this embodiment, the CuCrZr powder (commercially available) contained 0.25–0.65% Cr and 0.08–0.20% Zr, with the balance being Cu.
[0047] First, a 900-mesh stainless steel sieve was used to remove larger particles from the CuCrZr powder. Then, a 270-mesh steel sieve was used to remove smaller particles, resulting in spherical CuCrZr powder with a particle size between 15-53 μm and good flowability. This yielded an initial powder with good sphericity and flowability. For tungsten powder, a 2500-mesh steel sieve was used to remove larger particles, resulting in non-spherical tungsten powder with a particle size of approximately 5 μm. Graphene nanosheets were purchased from TOKYO CHEMICAL INDUSTRY CO.,LTD. The graphene nanosheets have a specific surface area of 300 m². 2 / g, the coating is prepared according to the following steps:
[0048] (1) Mix 108g CuCrZr powder and 1.08g graphene nanosheets. Use a planetary ball mill for low-energy mixing. The planetary ball mill rotates at 270rpm. The protective atmosphere is argon. Stop for 5 minutes after running for 15 minutes, and then continue running. Repeat this process until mixing for 5 hours to obtain a mixed powder of graphene nanosheets and CuCrZr powder (graphene copper alloy composite powder), denoted as Cu-GNPs powder.
[0049] (2) 109.08g of graphene-copper composite powder, 72g of CuCrZr powder, and 120g of W powder were mixed using a shaking mixing method at a speed of 100rpm for 15min to obtain a mixed powder, denoted as Cu40W-GNPs powder. Its SEM image is shown below. Figure 1 As shown.
[0050] (3) The above-mentioned mixed powder Cu40W-GNPs powder was sprayed using high-purity N2 as the spraying gas. The chamber pressure was 4.8 MPa, the chamber temperature was 750℃, the spraying distance was 30 mm, and the substrate was an ODS Cu alloy substrate (C15715 dispersion-strengthened copper alloy ODS alumina copper). The spray gun speed was 300 mm / s, and the spraying time was 5 min to obtain a Cu40W-GNP scoating with a thickness of 800 micrometers.
[0051] Comparative Example 1
[0052] The rest is the same as in Example 1, except that the specific coating preparation steps are as follows:
[0053] (1) Mix 180g CuCrZr powder and 120g W powder, and use a planetary ball mill for low-energy mixing. The planetary ball mill rotates at 270rpm, and the protective atmosphere is argon. After running for 15 minutes, stop for 5 minutes and then continue running. Repeat this process until mixing for 5 hours to obtain a mixed powder of tungsten powder and CuCrZr powder, which is denoted as Cu40W powder.
[0054] (2) The above-mentioned mixed powder Cu40W powder was sprayed using high-purity N2 as the spraying gas. The chamber pressure was 4.8 MPa, the chamber temperature was 750℃, the spraying distance was 30 mm, and the substrate was an ODS Cu alloy substrate (C15715 dispersion-strengthened copper alloy ODS alumina copper). The spray gun speed was 300 mm / s, and the spraying time was 5 min, resulting in a Cu40W coating with a thickness of 800 micrometers.
[0055] The mixed powders containing and without graphene nanosheets prepared in Example 1 and Comparative Example 1, as well as the corresponding coatings, were characterized and analyzed. The results are shown in the figure. Figures 2 to 6 .
[0056] XRD analysis of mixed powders and coatings, such as Figure 2 As shown, the main structures are the Cu phase of fcc and the W phase of bcc; Figure 3 Raman spectroscopy results showed successful incorporation of graphene into the powder and composite coating. Tribological performance was tested using tribological experiments, and the wear track morphology was measured using white light interferometry. The aluminum adhesion area was then statistically analyzed using software. The results are as follows: Figure 4 , Figure 5 and Figure 6 As shown in the figure (ODS Cu represents the ODS Cu substrate; Cu40W represents the coating obtained by spraying with Cu40W powder of Comparative Example 1; Cu40W-GNPs represents the coating obtained by spraying with Cu40W-GNPs powder of Example 1), by Figure 4-6It can be seen that the COF of the Cu40W-GNPs coating in Example 1 is 0.16, and the wear rate is 1.9 × 10⁻⁶. -5 mm 3 / N·m, its COF and wear rate compared to the substrate (ODS Cu) (0.61 and 24.8×10) -5 mm 3 The aluminum adhesion area was reduced by more than 3 times and by more than one order of magnitude, respectively, and the aluminum adhesion area was reduced by 40 times.
[0057] Comparative Example 2
[0058] The rest is the same as in Example 1, except that the coating preparation steps are as follows:
[0059] (1) 1.08g of graphene nanosheets, 180g of CuCrZr powder and 120g of W powder were directly mixed and low-energy mixing was carried out using a planetary ball mill at a speed of 270rpm. The protective atmosphere was argon. The mixture was stopped for 5 minutes after every 15 minutes of operation and then continued to operate. This process was repeated until the mixture was mixed for 5 hours to obtain a mixed powder of graphene nanosheets, CuCrZr powder and tungsten powder.
[0060] (2) The above-mentioned mixed powder was sprayed using high-purity N2 as the spraying gas. The chamber pressure was 4.8 MPa, the chamber temperature was 750℃, the spraying distance was 30 mm, and the substrate was ODS Cu alloy substrate (C15715 dispersion-strengthened copper alloy ODS alumina copper). The spray gun speed was 300 mm / s, and the spraying time was 5 min.
[0061] Experiments revealed that W powder exhibited severe agglomeration, while the alloyed copper powder showed significant deformation and poor flowability. Figure 7 The spraying process is affected, and a copper-tungsten-graphene composite coating cannot be obtained.
[0062] Comparative Example 3
[0063] The rest is the same as in Example 1, except that the coating preparation steps are as follows:
[0064] (1) 180g CuCrZr powder and 1.08g graphene nanosheets were directly mixed and low-energy mixing was carried out using a planetary ball mill with a speed of 270rpm and an argon protective atmosphere. The mixture was stopped for 5 minutes after every 15 minutes of operation and then continued to operate. This process was repeated until the mixture was mixed for 5 hours to obtain a mixed powder of graphene nanosheets and CuCrZr powder.
[0065] (2) The mixed powder of graphene nanosheets and CuCrZr powder obtained in step (1) is mixed with 120g of tungsten powder by oscillation mixing method, with the rotation speed set at 100rpm, and mixed for 15min to obtain mixed powder.
[0066] (3) The above-mentioned mixed powder Cu40W-GNPs powder was sprayed using high-purity N2 as the spraying gas. The chamber pressure was 4.8 MPa, the chamber temperature was 750℃, the spraying distance was 30 mm, and the substrate was ODS Cu alloy substrate (C15715 dispersion-strengthened copper alloy ODS alumina copper). The spray gun speed was 300 mm / s, and the spraying time was 5 min.
[0067] Experiments revealed that, possibly because graphene adhered to almost all of the copper powder, the plastic deformation bonding between particles was affected during cold spraying, resulting in a poor-quality copper-tungsten graphene composite coating that could not be used in experiments.
[0068] Comparative Example 2 directly mixed and ball-milled all powder types. Comparative Example 3 first ball-milled and mixed all alloy copper powder with graphene nanosheets, and then mixed them with tungsten powder. Experiments showed that neither yielded a copper-tungsten-graphene composite coating. Only by following the method in Example 1, first ball-milling and mixing a portion of the alloy copper powder with graphene nanosheets to disperse the graphene nanosheets on a portion of the alloy copper powder, and then mixing in the remaining un-graphene-adhered original alloy copper powder and the harder tungsten powder, followed by cold spraying, could the hindering effect of graphene on the plastic deformation between particles be effectively avoided. Simultaneously, graphene could be introduced into the composite coating without compromising its quality, resulting in a composite coating with low COF, low wear rate, and low aluminum adhesion. This is likely because graphene plays a role in interlayer shear lubrication in the composite coating, effectively inhibiting surface degradation and crack propagation. Furthermore, during adhesion, a graphene-rich friction layer is formed on the friction surface. Due to the large wetting angle between graphene and Al, aluminum adhesion is effectively suppressed.
[0069] Example 2
[0070] The rest is the same as in Example 1, except that the coating is prepared according to the following steps:
[0071] (1) Mix 70g CuCrZr powder and 0.8g graphene nanosheets. Use a planetary ball mill for low-energy mixing. The planetary ball mill rotates at 270rpm. The protective atmosphere is argon. Stop for 5 minutes after every 15 minutes of operation, and then continue to run. Repeat this process until mixing for 6 hours to obtain a mixed powder of graphene nanosheets and CuCrZr powder (graphene copper alloy composite powder), denoted as Cu-GNPs powder.
[0072] (2) Mix 70.8g of graphene copper composite powder, 90g of CuCrZr powder and 100g of W powder. Use a shaking mixing method, set the speed to 200rpm, and mix for 12min to obtain a mixed powder, which is represented as Cu40W-GNPs powder.
[0073] (3) The above-mentioned mixed powder Cu40W-GNPs powder was sprayed using high-purity N2 as the spraying gas. The chamber pressure was 4.5 MPa, the chamber temperature was 800℃, the spraying distance was 28 mm, and the substrate was an ODS Cu alloy substrate (C15715 dispersion-strengthened copper alloy ODS alumina copper). The spray gun speed was 280 mm / s, and the spraying time was 6 min, resulting in a Cu40W-GNPs coating with a thickness of 950 micrometers.
[0074] Example 3
[0075] The rest is the same as in Example 1, except that the coating is prepared according to the following steps:
[0076] (1) Mix 150g CuCrZr powder and 2g graphene nanosheets. Use a planetary ball mill for low-energy mixing. The planetary ball mill rotates at 270rpm. The protective atmosphere is argon. Stop for 5 minutes after every 15 minutes of operation, and then continue to run. Repeat this process until mixing for 4 hours to obtain a mixed powder of graphene nanosheets and CuCrZr powder (graphene copper alloy composite powder), denoted as Cu-GNPs powder.
[0077] (2) Mix 152g of graphene copper composite powder, 50g of CuCrZr powder and 140g of W powder. Use a shaking mixing method, set the speed to 150rpm, and mix for 20min to obtain a mixed powder, which is represented as Cu40W-GNPs powder.
[0078] (3) The above-mentioned mixed powder Cu40W-GNPs powder was sprayed using high-purity N2 as the spraying gas. The chamber pressure was 4.8 MPa, the chamber temperature was 780℃, the spraying distance was 32 mm, and the substrate was an ODS Cu alloy substrate (C15715 dispersion-strengthened copper alloy ODS alumina copper). The spray gun speed was 310 mm / s, and the spraying time was 4 min, resulting in a Cu40W-GNP scoating with a thickness of 640 micrometers.
[0079] In this invention, a copper-tungsten graphene coating is prepared using a high-pressure cold spraying process. This process offers advantages such as low oxide content, high spraying efficiency, high hardness, and good bonding strength. It also inhibits Cu oxidation and reduces defects such as cracks and porosity. Furthermore, the resulting coating is thick and of high quality, making it suitable for direct preparation of electromagnetic launch track coatings. This method is particularly applicable to the field of electromagnetic launch copper track lubrication and wear-resistant coating production technology, and is especially suitable for a cold-sprayed copper-tungsten graphene coating method and product exhibiting ultra-low friction coefficient, wear rate, and ultra-high anti-aluminum adhesion capability.
[0080] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing a cold-sprayed copper-tungsten graphene coating, characterized in that, The mixture of CuCrZr alloy powder, W powder and graphene nanosheets was prepared by high-pressure cold spraying onto a substrate. The mass ratio of CuCrZr alloy powder, W powder, and graphene nanosheets in the mixed powder is (160-200):(100-140):(0.5-2). The mixed powder of CuCrZr alloy powder, W powder, and graphene nanosheets was obtained according to the following method: A portion of CuCrZr alloy powder and graphene nanosheets are first ball-milled and mixed to obtain graphene copper alloy composite powder. Then, the prepared graphene copper alloy composite powder is mixed with W powder and the remaining CuCrZr alloy powder to obtain the mixed powder. The portion of CuCrZr alloy powder accounts for 40-80 wt% of the total CuCrZr alloy powder. The high-pressure cold spraying process has a spraying chamber pressure of 4.5–4.8 MPa and a chamber temperature of 750–800 °C.
2. The preparation method according to claim 1, characterized in that, The CuCrZr alloy powder in the mixed powder has a particle size of 10–100 μm, and the W powder has a particle size of less than or equal to 8 μm; the graphene nanosheets have a specific surface area of 200–400 m². 2 / g.
3. The preparation method according to claim 1, characterized in that, The CuCrZr alloy powder contains 0.1-0.8% Cr by mass, 0.05-0.25% Zr by mass, and the balance is Cu.
4. The preparation method according to claim 1, characterized in that, The high-pressure cold spraying uses high-purity nitrogen or high-purity argon as the spraying gas. The spraying distance is 28-32mm, and the gun speed is 275-325mm / s.
5. The cold-sprayed copper-tungsten graphene coating prepared by the preparation method according to any one of claims 1 to 4.
6. An electromagnetic launch track, characterized in that, The track surface is provided with a cold-sprayed copper-tungsten graphene coating as described in claim 5.
7. The electromagnetic launch track as described in claim 6, characterized in that, The thickness of the cold-sprayed copper-tungsten graphene coating is 500–1000 µm.
8. The electromagnetic launch track as described in claim 6, characterized in that, The substrate is a dispersion-strengthened copper alloy or beryllium copper.
Citation Information
Patent Citations
Method for preparing uniform and dense W-Cu composite material with high tungsten content
CN102363852A
Graphene / copper composite material and preparation method thereof
CN111593226A
Copper-tungsten alloy material, preparation method therefor, and application thereof
WO2022068812A1